2014
DOI: 10.1136/bmjopen-2014-005049
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between the expression of hEag1 and HIF-1α in breast cancers: an observational study

Abstract: ObjectivesTo explore the expression patterns of Eag1 (ether á go-go 1) and HIF-1α (hypoxia-inducible factor 1α) in a cohort of patients with breast cancer.SettingDepartment of general surgery in an upper first-class hospital in Xi'an, China.ParticipantsA total of 112 female Han Chinese patients with a diagnosis of invasive ductal carcinoma were included. Patients with main internal diseases, such as cardiovascular, endocrine, gastroenterological, haematological, infectious diseases, etc, were excluded.Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…The expression of HIF-1a has been correlated to K v 10.1 level in breast cancer tissues. 142 These data are in agreement with those obtained in cell lines, showing that K v 10.1 expression increases HIF-1a levels and thus VEGF secretion, inducing tumor vascularization. 73,97 Resistance to hypoxic condition could also be enhanced by the overexpression of the K 2P channel KCNK9 in human breast and small-cell lung tumors.…”
supporting
confidence: 90%
“…The expression of HIF-1a has been correlated to K v 10.1 level in breast cancer tissues. 142 These data are in agreement with those obtained in cell lines, showing that K v 10.1 expression increases HIF-1a levels and thus VEGF secretion, inducing tumor vascularization. 73,97 Resistance to hypoxic condition could also be enhanced by the overexpression of the K 2P channel KCNK9 in human breast and small-cell lung tumors.…”
supporting
confidence: 90%
“…Kv10.1 expression is mostly restricted to the central nervous system under healthy conditions. However, noticeable Kv10.1 levels are detected in clinical tumors from several different origins, including neuroblastomas [56], glioblastomas and derived brain metastasis [21], breast cancer [57,58], colon and gastric cancers [59,60], or osteosarcomas [61,62]. This evidence supports Kv10.1 as a potential marker for several cancers, such as cervical and colon cancer.…”
Section: Kv Channels and Cancermentioning
confidence: 65%
“…The authors have demonstrated that blocking hEag1 with astemizole or silencing induces the breast cancer depolarization and consequently reduces the calcium influx and the cell migration without any influence on the cell proliferation [97]. These data are clinically valuable as hEAG1 are overexpressed in invasive ductal carcinoma breast cancer or metastatic lymph nodes [97,132] and their co-expression with HIF-1α is correlated with tumor size, lymph node status, and tumor stage [132], and the possibility of pharmacologically blocking these channels might represent a promising therapy. Moreover, astemizole may be used to pharmacologically discriminate hEAG from the related hERG potassium channels in MCF-7 breast cancer cells [133].…”
Section: Heag1 Channels As Pharmacological Targets In Breast Cancermentioning
confidence: 99%